Populist political ideation and communication of gubernatorial candidates in Indonesia’s 2018 gubernatorial elections: Anti-establishment views, secular nationalism and Islamism as ideational-populist elements - Ahmad, Nyarwi (2022)
Populism has been evolving across the globe. Knowledge of the ways and degree to which political actors in Asian democracy exploited anti-establishment views, secular nationalism and Islamism as ideational elements when they established populist political communication strategies for local elections has, however, been under-developed. Focusing on such issues, this work selects gubernatorial candidates who ran in Indonesia’s 2018 gubernatorial elections as cases, using extracts from materials they posted on their Facebook pages. The findings are as follows. Candidates did not merely advocate anti-establishment views, but also adopted secular nationalism and Islamism as ideational-populist elements for developing populist political communication strategies. Those who exploited anti-economic elites favoured establishing secular nationalist and Islamic-based populist political communication strategies inclusively. Those who propagated anti-economic, anti-political and anti-bureaucratic elites instead greatly preferred advancing an Islamic populist political communication strategy. However, through employing such efforts, only few succeeded in these elections. © The Author(s) 2020.